Amorphous metal composite oxide catalyst as well as preparation method and application thereof

By preparing a 30% TiO2-ZrO2 amorphous composite oxide catalyst, the problem of insufficient catalytic activity of existing photocatalysts in the selective oxidation of methane was solved, the effect of efficient generation of methanol and formaldehyde was achieved, and the performance of the photocatalyst was improved.

CN120605703APending Publication Date: 2025-09-09BIOGAS SCI RES INST MIN OF AGRI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510699520.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

Existing photocatalysts are insufficiently modified in the field of methane selective oxidation, and the influence of the crystal structure of semiconductor photocatalysts on the adsorption intensity of reactants and intermediate species and the efficiency of photogenerated carrier separation has not been fully studied, resulting in insufficient catalytic activity.

Method used

A 30% TiO2-ZrO2 amorphous composite oxide catalyst is prepared by a spray method in a high-temperature flame, keeping ZrO2 in an amorphous state to form a nanocomposite material for photocatalytic methane oxidation to generate high-value-added liquid products methanol and formaldehyde.

Benefits of technology

The selective oxidation of methane to methanol and formaldehyde achieved 100% product selectivity, increased the generation of photogenerated electron-hole pairs, reduced electrochemical impedance, and enhanced the stability and efficiency of the photocatalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120605703A_ABST
    Figure CN120605703A_ABST
Patent Text Reader

Abstract

The invention discloses an amorphous metal composite oxide catalyst as well as a preparation method and application thereof, and belongs to the technical field of metal oxide-based catalysts. The invention provides an amorphous metal composite oxide catalyst. The expression of the amorphous metal composite oxide catalyst is 30% by mole of TiO2-ZrO2-A, zrO2 in the 30% TiO2-ZrO2-A is in an amorphous state, and TiO2 in the 30% TiO2-ZrO2-A is in a crystalline state. When the catalyst disclosed by the invention is used for photocatalytic methane oxidation, liquid products only generate CH3OH and HCHO, and the C1 product selectivity reaches 100%. After the amorphous ZrO2 is compounded, the oxygen vacancy of the catalyst is increased, the electrochemical impedance is reduced, the generated photo-induced electron hole pairs are increased, and the prepared amorphous metal oxide composite photocatalyst is applied to the field of photocatalytic methane oxidation for the first time. Compared with the prior art, the method has the comprehensive advantages of mild reaction conditions, cost effectiveness and the like, has huge potential in future development, is expected to be widely applied to more fields, and forms complementation with other catalytic technologies to jointly promote the sustainable development process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal oxide-based catalysts, and in particular relates to an amorphous metal composite oxide catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, China has made significant progress in the field of photothermal catalytic methane selective oxidation. Photothermal catalytic methane selective oxidation catalysts mainly include three categories: precious metals, non-precious metals and non-metallic bases. Precious metal catalysts mainly include Ru, Rh, Pt, Pd and Au, among which Ru is the cheapest platinum group metal, and Ru-based catalysts have been studied more. Non-precious metal-based catalysts mainly include nano-metal oxides such as ZnO, TiO2, Fe2O3, etc., while non-metal-based catalysts mainly include some sulfides (MoS2, ZnIn2S4, CdS, etc.), carbides (C3N4, graphene, etc.) and other materials. Domestic research institutions and universities, such as the Chinese Academy of Sciences, Tsinghua University, Xiamen University, etc., have invested a lot of resources in research in this field. In terms of catalyst design and optimization, domestic researchers have developed a variety of catalysts with high catalytic activity. For example, the molecular sieve-loaded Au nanoparticles (Au / H-MOR) prepared by Wang et al. can selectively oxidize methane to methanol (CH3OH) at 150°C with a yield of 1300 μmol g cat -1 h -1 or 280 mmol g Au -1 h -1 , with a selectivity of 75%. Both hydroxyl radicals (·OH) and hydrogen peroxide participate in the activation and conversion of methane. Fang et al. used quantum-sized BiVO4 nanoparticles as catalysts and O2 as an oxidant to selectively photocatalyze the oxidation of methane at room temperature, achieving a selectivity of 96.6% for methanol. The activation of methane by hydroxyl radicals determines the reaction rate. These catalysts demonstrated excellent catalytic performance for the selective oxidation of methane to products such as CH3OH and formaldehyde (HCHO).

[0003] Although there are endless types of catalysts on the market, and many different types of functional nanomaterials have been developed, including alloys, metal oxides, etc., studies have shown that unmodified photocatalysts still face some difficult-to-overcome defects. Therefore, it is usually necessary to modify the photocatalyst to further construct high-quality functional materials with excellent overall photocatalytic performance. The atomic arrangement and coordination of specific crystal faces of semiconductor photocatalysts have a significant effect on the adsorption strength of reactants and intermediate species. In addition, semiconductor photocatalysts with different crystal face exposures will affect the separation efficiency and migration direction of photogenerated carriers, resulting in different photocatalytic activities. Despite this, there are relatively few systematic studies on the effects of co-catalyst modification and semiconductor crystal face structure on photocatalytic methane conversion and its reaction pathway. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide an amorphous metal composite oxide catalyst and its preparation method and application. The amorphous metal composite oxide catalyst prepared by the present invention is a light absorption carrier, which utilizes solar energy to selectively oxidize methane to generate high-value-added liquid products, thereby increasing the value of methane and facilitating transportation.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides an amorphous metal composite oxide catalyst having an expression in mole percentage of 30% TiO2-ZrO2-A;

[0007] The molar ratio of TiO2 to ZrO2 in the 30% TiO2-ZrO2-A is 3:7;

[0008] ZrO2 is amorphous and TiO2 is crystalline.

[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned amorphous metal composite oxide catalyst, comprising the following preparation steps:

[0010] S1. Tetrabutyl titanate as a TiO2 precursor, zirconium tetrachloride as a ZrO2 precursor, according to the molar ratio of TiO2 to ZrO2 3:7 weighed tetrabutyl titanate and zirconium tetrachloride dissolved in ethanol to obtain a mixed precursor solution;

[0011] S2. Spraying the mixed precursor solution into a high temperature area for reaction, and then rapidly cooling and filtering to obtain an amorphous metal composite oxide catalyst.

[0012] Preferably, the concentration of the mixed precursor solution in S1 is 0.1-0.2 mol / L.

[0013] Preferably, the spray feed rate in S2 is 3 mL / min; the spray particle size is 1-5 μm.

[0014] Preferably, the temperature of the high temperature area in S2 is 800-1000°C.

[0015] More preferably, the high-temperature region is a high-temperature flame, the flame temperature is controlled at 800-1000°C, the spray feed rate is 3 mL / min, and the hydrogen flow rate is 3.3 L / min. The flame method can provide an extremely high cooling rate, enabling rapid and uniform mixing and reaction of the precursors. By adjusting parameters such as the spray rate, gas flow rate, and flame temperature, the reaction conditions can be precisely controlled to optimize the properties of the nanocomposite material.

[0016] Preferably, the reaction time of spraying to the high temperature area in S2 is 3 to 30 seconds.

[0017] Preferably, the amorphous metal composite oxide catalyst obtained in S2 may be calcined at 300-400° C. to remove organic residues, and the calcination time is 2-4 hours.

[0018] Preferably, the particle size of the amorphous metal composite oxide catalyst is 5 to 30 nm.

[0019] In a third aspect, the present invention provides the use of the above-mentioned amorphous metal composite oxide catalyst or the amorphous metal composite oxide catalyst prepared by the preparation method in photocatalytic methane oxidation, wherein the liquid products after the catalytic reaction are only methanol and formaldehyde.

[0020] Under light, both H2O and methane participated in the reaction, forming ·CH3O and ·OH free radical intermediates to generate CH3OH and HCHO.

[0021] Contains at least the following beneficial technical effects:

[0022] The catalyst of the present invention produces only CH3OH and HCHO as liquid products in photocatalytic methane oxidation, with a C1 product selectivity of 100%. After compounding with amorphous ZrO2, the catalyst oxygen vacancies increase, the electrochemical impedance decreases, and the generation of photogenerated electron-hole pairs increases.

[0023] The amorphous metal oxide composite photocatalyst prepared by the present invention is applied to the field of photocatalytic methane oxidation for the first time.

[0024] Compared with traditional thermal catalysis and electrocatalysis, photocatalytic technology has many significant advantages. Photocatalysis uses solar energy as energy, which is a renewable and clean energy source. It not only reduces dependence on traditional fossil fuels, but also avoids high energy consumption and complex equipment requirements caused by high temperature and high pressure conditions, thereby significantly reducing operating costs and environmental burdens. Photocatalytic reactions are usually carried out at room temperature and pressure, with mild conditions and simple operation, which makes it more feasible in large-scale applications. Although photocatalytic technology still faces challenges in terms of photogenerated carrier separation efficiency and catalyst stability, its comprehensive advantages in energy utilization, environmental friendliness, mild reaction conditions and cost-effectiveness give it great potential for future development. It is expected to be widely used in more fields and complement other catalytic technologies to jointly promote the process of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a diagram of the 30% TiO2-ZrO2-A photocatalytic methane oxidation reaction equipment in Example 1 of the present invention.

[0026] Figure 2 The 30% TiO2-ZrO2-A product in Example 1 of the present invention 1 H NMR spectrum.

[0027] Figure 3 Schematic diagram of the structure and XRD pattern of 30% TiO2-ZrO2-A in Example 1 of the present invention.

[0028] Figure 4 This is a TEM image of the morphology analysis of 30% TiO2-ZrO2-A in Example 1 of the present invention.

[0029] Figure 5 This is the XPS graph of 30% TiO2-ZrO2-A in Example 1 of the present invention

[0030] Figure 6 The EPR-O of 30% TiO2-ZrO2-A in Example 1 of the present invention v Spectrum.

[0031] Figure 7 The photoelectric performance diagram of the 30% TiO2-ZrO2-A product in Example 1 of the present invention is shown in Figures a and b, respectively, are UV-vis DRS diagrams and their corresponding Tauc diagrams; c is an electrochemical impedance spectroscopy diagram; d and e are in situ EPR-photogenerated h + Spectrum; f is the 30% TiO2-ZrO2-A mechanism diagram.

[0032] Figure 8 This is the In suit-FTIR chart of the 30% TiO2-ZrO2-A product in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] Based on the embodiments of the present invention, all other embodiments obtained by persons of ordinary skill in the art without creative work shall fall within the scope of protection of the present invention. The present invention will be described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0034] Example 1

[0035] A method for preparing an amorphous metal oxide composite photocatalyst comprises the following steps:

[0036] (1) Tetrabutyl titanate was used as a precursor of TiO2, and zirconium tetrachloride was used as a precursor of ZrO2. Tetrabutyl titanate and zirconium tetrachloride were weighed and dissolved in ethanol at a molar ratio of TiO2 to ZrO2 of 3:7 to obtain a mixed precursor solution with a concentration of 0.15 mol / L.

[0037] (2) The precursor solution is atomized into fine droplets through a spray device and sprayed into a high-temperature flame. The flame temperature is controlled at 800°C, the spray feed rate is 3 mL / min, and the hydrogen flow rate is 3.3 L / min. In the flame, the precursor droplets rapidly decompose and react to form a 30% TiO2-ZrO2-A nanocomposite material, which is then rapidly cooled by water cooling to maintain the amorphous state of ZrO2. Finally, the generated nanoparticles are collected and low-temperature calcined at 350°C to remove organic residues while avoiding ZrO2 crystallization. The entire process is simple to operate and suitable for large-scale industrial production. By precisely controlling the reaction conditions, a 30% TiO2-ZrO2-A nanocomposite material with amorphous ZrO2 can be effectively prepared.

[0038] Example 2

[0039] A method for preparing an amorphous metal oxide composite photocatalyst comprises the following steps:

[0040] (1) Tetrabutyl titanate was used as a precursor of TiO2, and zirconium tetrachloride was used as a precursor of ZrO2. Tetrabutyl titanate and zirconium tetrachloride were weighed and dissolved in ethanol at a molar ratio of TiO2 to ZrO2 of 3:7 to obtain a mixed precursor solution with a concentration of 0.1 mol / L.

[0041] (2) The precursor solution is atomized into fine droplets through a spray device and sprayed into a high-temperature flame. The flame temperature is controlled at 900°C, the spray feed rate is 3 mL / min, and the hydrogen flow rate is 3.3 L / min. In the flame, the precursor droplets rapidly decompose and react to form a 30% TiO2-ZrO2-A nanocomposite material, which is then rapidly cooled by water cooling to maintain the amorphous state of ZrO2. Finally, the generated nanoparticles are collected and low-temperature calcined at 300°C to remove organic residues while avoiding ZrO2 crystallization. The entire process is simple to operate and suitable for large-scale industrial production. By precisely controlling the reaction conditions, a 30% TiO2-ZrO2-A nanocomposite material with amorphous ZrO2 can be effectively prepared.

[0042] Example 3

[0043] A method for preparing an amorphous metal oxide composite photocatalyst comprises the following steps:

[0044] (1) Tetrabutyl titanate was used as a precursor of TiO2, and zirconium tetrachloride was used as a precursor of ZrO2. Tetrabutyl titanate and zirconium tetrachloride were weighed and dissolved in ethanol at a molar ratio of TiO2 to ZrO2 of 3:7 to obtain a mixed precursor solution with a concentration of 0.2 mol / L.

[0045] (2) The precursor solution is atomized into fine droplets through a spray device and sprayed into a high-temperature flame. The flame temperature is controlled at 1000°C, the spray feed rate is 3 mL / min, and the hydrogen flow rate is 3.3 L / min. In the flame, the precursor droplets rapidly decompose and react to form a 30% TiO2-ZrO2-A nanocomposite material, which is then rapidly cooled by water cooling to maintain the amorphous state of ZrO2. Finally, the generated nanoparticles are collected and low-temperature calcined at 400°C to remove organic residues while avoiding ZrO2 crystallization. The entire process is simple to operate and suitable for large-scale industrial production. By precisely controlling the reaction conditions, a 30% TiO2-ZrO2-A nanocomposite material with amorphous ZrO2 can be effectively prepared.

[0046] Comparative Example 1

[0047] The 30% TiO2-ZrO2-A prepared in Example 1 was placed in a tube furnace and sintered at 800°C in air atmosphere for 2 hours at a heating rate of 5°C / min. After sintering, it was cooled to room temperature, taken out, and ground to obtain TiO2-ZrO2-A800.

[0048] Experimental Example 1

[0049] Application of amorphous metal oxide composite photocatalyst 30% TiO2-ZrO2-A in photocatalytic methane oxidation. The 30% TiO2-ZrO2-A photocatalyst prepared in Example 1 was subjected to photocatalytic methane oxidation (at Figure 1 The photocatalytic methane oxidation reaction test was carried out in a 100 mL stainless steel autoclave equipped with two sapphire windows to allow light irradiation. Typically, 5 mg of catalyst was dispersed in 50 mL of water by ultrasonic treatment for 10 min. Then, the mixture was added to the autoclave and the temperature was set to 298 K. After sealing and purging with ultrapure O2 (99.999 vol%) for 30 minutes, 2 bar O2 (99.999% purity) and 18 bar CH4 (99.99% purity) were flowed into the autoclave. Subsequently, the solution was stirred at 500 rpm and a 300 W xenon lamp was used as a light source. The autoclave was equipped with a temperature probe and a pressure probe to measure the liquid temperature and gas pressure, respectively. During the reaction, the heater was turned on at the same time. After the reaction, the autoclave was cooled to below 283 K in an ice bath, and the gas and liquid products were then collected with a gas bag and a brown bottle, respectively. The liquid product was passed through 1 H NMR detection ( Figure 2 ), in addition to the water peak at 4.7 ppm and the DMSO peak at 2.6 ppm, only the CH3OH peak appeared at 3.2 ppm, and the yield was 2259.7 μmol·g cat -1 At the same time, the HCHO content was detected by acetylacetone colorimetry and was 2532 μmol·g cat -1 , the liquid products only produced CH3OH and HCHO, and the C1 product selectivity reached 100%.

[0050] Experimental Example 2

[0051] Morphology and structure analysis of 30% TiO2-ZrO2-A. The 30% TiO2-ZrO2-A prepared in Example 1 was first characterized by XRD ( Figure 3 b), it can be found that the classic amorphous peaks are present at the 2θ diffraction angle of 25° to 40°, and the two obvious peaks correspond to the (101) and (200) crystal planes in the diffraction data of the anatase TiO2 standard sample (JCPDS No.21-1272). 30% TiO2-ZrO2-A800 photocatalyst, ZrO2 is tetragonal phase, in XRD Figure 3In b, several characteristic peaks of ZrO2 correspond to the (101), (110), (112), (211), and (220) crystal planes of the standard sample diffraction data of ZrO2 (JCPDS No. 37-1413). In order to further confirm the amorphous ZrO2, the lattice gap of ZrO2 that cannot be measured was found on the high-magnification AC-STEM ( Figure 4 d, e), the (101) and (200) crystal planes of TiO2 can be observed, further verifying the crystal structure.

[0052] Experimental Example 3

[0053] The surface elements and molecular composition of 30% TiO2-ZrO2-A prepared in Example 1 were determined and characterized by XPS. From the full spectrum, it can be seen that the surface chemical composition is Ti, Zr, O ( Figure 5 a). Figure 5 b Ti 2p spectrum shows that Ti 2p 3 / 2 and 2p 1 / 2 The characteristic double peaks of Ti orbitals, with an energy difference of 5.7 eV between the two, confirm the Ti 4+ The valence state of TiO2 was confirmed. Figure 5 It can be observed in c that 30% TiO2-ZrO2-A forms a Zr-O bond at around 182 eV, and 3d 3 / 2 and 3D 5 / 2 The energy difference between the double peaks of the orbital is 2.4 eV, which further confirms that Zr 4+ valence state. And from Figure 5 d and Figure 6 It can be seen that 30% TiO2-ZrO2-A has more oxygen vacancies.

[0054] Experimental Example 4

[0055] The photoelectric performance of 30% TiO2-ZrO2-A prepared in Example 1 was analyzed. In order to investigate the light absorption performance, UV-vis DRS was used to characterize it. Figure 7 a, b), UV-visible diffuse reflectance absorption spectrum shows that the E g The energy of Eg is slightly lower than that of TiO2-ZrO2-A800 by 3.4 eV. The narrowing of Eg is attributed to the lattice disorder effect of amorphous ZrO2. Electrochemical impedance spectroscopy (EIS) measurements were also performed to analyze the charge transfer behavior of 30% TiO2-ZrO2-A ( Figure 7 c), the charge transfer resistance (Rct) of 30% TiO2-ZrO2-A is small, indicating that amorphous ZrO2 helps electron transfer and inhibits charge recombination, thereby improving photooxidation activity, and in situ EPR ( Figure 7d, e) It can be seen that 30% TiO2-ZrO2-A produces more photogenerated h + This further demonstrates that 30% TiO2-ZrO2-A has good overall photoelectric properties.

[0056] Experimental Example 5

[0057] A preliminary mechanism analysis of the photocatalytic methane oxidation of Example 2 was conducted, and the free radical transformation during the reaction was analyzed by testing In suit-FTIR ( Figure 8 ), thus making a preliminary prediction of the entire reaction. Some CH4 (1340 and 3000 cm -1 ) and hydroxyl groups (·OH, at 1650 cm -1 ) absorption band. It is worth noting that the absorption band of CH3O is at 2824cm -1 This indicates that the CH bond in the methane molecule dissociates and CH3O species are produced on 30% TiO2-ZrO2-A. These two groups are considered to be key intermediates in the direct oxidation of methane to CH3OH and HCHO. Based on these results, a mechanism for the photocatalytic oxidation of methane to CH3OH and HCHO on 30% TiO2-ZrO2-A was proposed, as shown in Figure 2. Figure 7 f. In this process, electron-hole pairs are generated when absorbing photons with energy equal to or higher than 30% of the TiO2-ZrO2-A band gap. Subsequently, water can be photogenerated + Oxidation (or reduction with O2) produces free OH radicals. The initial step in the activation of methane on 30% TiO2-ZrO2-A involves reaction with OH radicals. These OH radicals then react with CH3 radicals to form CH3OH. CH3OH can then be converted to HCHO through oxidation.

[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. An amorphous metal composite oxide catalyst, characterized in that Its expression in mole percentage is 30% TiO2-ZrO2-A; The molar ratio of TiO2 to ZrO2 in the 30% TiO2-ZrO2-A is 3:7; ZrO2 is amorphous and TiO2 is crystalline.

2. The method for preparing the amorphous metal composite oxide catalyst according to claim 1, characterized in that: The method comprises the following preparation steps: S1. Tetrabutyl titanate as a TiO2 precursor, zirconium tetrachloride as a ZrO2 precursor, according to the molar ratio of TiO2 to ZrO2 3:7 weighed tetrabutyl titanate and zirconium tetrachloride dissolved in ethanol to obtain a mixed precursor solution; S2. Spraying the mixed precursor solution into a high temperature area for reaction, and then rapidly cooling and filtering to obtain an amorphous metal composite oxide catalyst.

3. The preparation method according to claim 2, characterized in that The concentration of the mixed precursor solution in S1 is 0.1-0.2 mol / L.

4. The preparation method according to claim 2, characterized in that The spray feed rate in S2 is 3 mL / min; the spray particle size is 1-5 μm.

5. The preparation method according to claim 2, characterized in that The temperature of the high temperature area of ​​S2 is 800-1000°C.

6. The preparation method according to claim 2, characterized in that The time for spraying to the high temperature area for reaction in S2 is 3 to 30 seconds.

7. The preparation method according to claim 2, characterized in that The amorphous metal composite oxide catalyst obtained in S2 can also be calcined at 300-400° C. to remove organic residues, and the calcination time is 2-4 hours.

8. Use of the amorphous metal composite oxide catalyst according to claim 1 or the amorphous metal composite oxide catalyst prepared by the preparation method according to any one of claims 2 to 7 in photocatalytic methane oxidation, characterized in that: The liquid products after the catalytic reaction are only methanol and formaldehyde.